Pengaruh Tingkat Pendidikan terhadap Integritas Pegawai DPRD Kota Bukittinggi - Ashilah Puti Salsabila Arfi; Syamsir Syamsir (Policy, Law and Political Research Center, 2022)
This study aims to see how much influence the level of education has on the integrity of employees who work in the DPRD of Bukittinggi City. The total sample in this study was 61 respondents drawn using the Yamane formula with a significance level of 5%. The sampling technique in this study is Proportional Random Sampling. The data collection technique in this study used a questionnaire which was distributed to respondents with an ordinal scale measurement. Data analysis in this study is a non-parametric statistical test using the Spearman Rank Test. Using the SPSS 22 program as a data processing tool. The results of this study indicate that the test results show a value of 0.655 which states that the relationship or influence of the education level variable on employee integrity is not significant, because the value is greater than 0.05